Advantage of 16S rRNA amplicon sequencing in Helicobacter pylori diagnosis. Issue 3 (17th February 2021) - Gantuya, Boldbaatar; El Serag, Hashem B.; Saruuljavkhlan, Batsaikhan; Azzaya, Dashdorj; Matsumoto, Takashi; Uchida, Tomohisa; Oyuntsetseg, Khasag; Oyunbileg, Nyamdorj; Davaadorj, Duger; Yamaoka, Yoshio
Abstract: Background: 16S rRNA amplicon sequencing is an accurate method of detecting microbial infection without culture. It is unclear if sequencing has additional benefits over routine diagnostic methods for Helicobacter pylori testing. Methods: We enrolled Mongolian volunteers with dyspepsia. Using routine diagnostic methods, positive H .  pylori was defined as positive results on histology/immunohistochemistry, culture, rapid urease test, or serology; negative H .  pylori was defined by negative results from all these tests. We performed 16S rRNA sequencing on gastric biopsy specimens and calculated cutoffs for operational taxonomic units (OTUs) and relative abundance (RA) to define positive results using ROC curves. Results: We examined 161 individuals with a mean age of 43.6 years, and 64.6% were women. Using routine diagnostic methods, 122 (75.8%) participants were H .  pylori positive, the sensitivity and specificity for 16S rRNA sequencing were 94.3% and 82.1% or 93.4% and 82.1% when cutoff values were set to 1113 (OTU number) or 4.4% RA, respectively (both p  < .001). When combining the validated values, the concordance rate was high (91.1%); however, 16S rRNA sequencing had additional positive yield in 9 cases (5.6%) compared with routine diagnostic methods, and much greater additional positive yield compared to histopathology/IHC, culture, RUT, serology separately with 12 (7.4%), 37 (23.0%) and 43 (26.7%). Conclusion: 16S rRNA amplicon sequencing detects potentially important proportion of H .  pylori ‐positive cases that test negative with routine diagnostic methods. The quantitative number of H .  pylori can help to understand how it can be changing by diseases and RA give opportunity to understand how H .  pylori communicate with other microbiota.